Safety of a feed additive consisting of a tincture derived from the roots of Gentiana lutea L. (gentian tincture) for all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety of a tincture derived from Gentiana lutea L. (gentian tincture). It is intended to be used as a sensory additive for all animal species. The product is a water/ethanol solution, with a dry matter content of approximately 4.3% and it contains on average 0.0836% polyphenols (of which 0.0463% are flavonoids and 0.0027% xanthones) and 0.0022% gentiopicroside. The additive is intended for use in complete feed or drinking water up to a maximum level of 50 mg tincture/kg for all animal species, except horses, for which the proposed use is 200 mg/kg in complete feed. In a previous assessment, due to the genotoxic potential identified in vitro for xanthones (gentisin and isogentisin) and gentiopicroside the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) could not conclude on the safety of the additive for long‐living animals and on risks of genotoxicity and carcinogenicity for dermal exposure of unprotected users. The additive did not raise safety concern for short‐living animals, consumers and the environment. The applicant has provided information in the form of literature to address the previously identified genotoxic activity of xanthones and gentiopicroside and the risk for the user. Considering that the literature identified provided no new evidence, the FEEDAP Panel reiterated that it is not in a position to conclude on the safety of the additive for long‐living and reproductive animals. No conclusions could be drawn on the potential of the additive to be a dermal/eye irritant or a skin sensitiser. When handling the tincture, exposure of unprotected users to xanthones (gentisin and isogentisin) and gentiopicroside cannot be excluded. Therefore, to reduce the risk, the exposure of the users should be minimised.